Potential lessons from the Taiwan and New Zealand health responses to the COVID-19 pandemic (2020)
Approaches to preventing or mitigating the impact of the COVID-19 pandemic have varied markedly between nations. We examined the approach up to August 2020 taken by two jurisdictions which had successfully eliminated COVID-19 by this time: Taiwan and New Zealand. Taiwan reported a lower COVID-19 incidence rate (20.7 cases per million) compared with NZ (278.0 per million). Extensive public health infrastructure established in Taiwan pre-COVID-19 enabled a fast coordinated response, particularly in the domains of early screening, effective methods for isolation/quarantine, digital technologies for identifying potential cases and mass mask use. This timely and vigorous response allowed Taiwan to avoid the national lockdown used by New Zealand. Many of Taiwan’s pandemic control components could potentially be adopted by other jurisdictions.